Eksplorasi Tumbuhan Lokal Asal Budong-Budong Sebagai Obat Traditional, Bahan Kecantikan Dan Kebugaran - Tahar, Musrifah; Isdaryanti, Isdaryanti; Wiyarzah, Ice; Mardewi, Mardewi; JA, Puspita Hadriani; Puspa, Rati; Khaerunnisa, Khaerunnisa (Universitas Gajah Putih, 2023)
The Budong-Budong community, Topoyo District, Central Mamuju Regency, West Sulawesi Province is known as a community that uses many plants for various functions in their activities. The purpose of this research was to eksplore the types of local plants that used in traditional medicine, beauty and fitness ingredients. This research used descriptive qualitative method with data collection method are carried out by interviewing, observing and literature studying. The results showed that there are 40 types of local plants that were used both as herbal medicines, beauty and fitness ingredients. The parts of the plant used are leaves, flowers, seeds, fruit, skin, rhizomes and tubers. The parts of plants that have the most functions are leaves and fruit.